STUDI KIMIA SENYAWA GLIKOSIDA TUMBUHAN SUNGKEI, PERONEMA CANESCENS (VERBENACEAE) - Partomuan Simanjuntak (Research Center for Chemistry - LIPI, 1996)
Two glycoside compounds from methanol extract of Peronema canescens Jack. (Verbenaceae) were isolated and elucidated using on the basis of Nuclear magnetic resonances (1H-, 13C-NMR), mass and ultra-violet (with diagnostic reagent).